The making and unmaking of empires Britain, India, and America c.1750-1783 - Marshall, P. J. (Peter James) (Oxford University Press, 2007)
P.J. Marshall deals with a crucial period in the history of the British empire in trying to explain how the British at the same time lost an empire in North America, while winning one in parts of India. He shows that British objectives were much the same all over the world.